BRAND EQUITY DEVELOPMENT STRATEGY TO ENHANCE THE COMPETITIVENESS OF FOOD SMALL-MEDIUM ENTERPRISE'S (SMES): CASE STUDIES ON FUDIA-POLINELA AGRI-FOOD CENTRE - Fitriani, Fitriani; Sutarni, Sutarni; Unteawati, Bina; Apriyani, Marlinda; Widyawati, Dewi Kania; Berliana, Dayang (Jurnal AGRISEP, 2021)
The competitiveness of local agri-food needs through various marketing strategies. An essential part of the company's marketing strategy and tactics is recognizing product brand equity in the market. This study aims to identify brand entities, brand communication, and process to build Brand Equity toward local SMEs' competitiveness. A case study approach did at one of the SMEs in Bandar Lampung on the "FUDIA-Center of Agri-Food Polinela," that produce FUDIA cake & bakery.  The research has conducted from April to July 2020. Data analysis used a qualitative descriptive approach using SWOT analysis and a brand development model for SMEs. The analysis results concluded that FUDIA's brand recognition is the initial stage.  Development of the Fudia brand equity must take into account an existing market and expanding market share.  Enhancement market share could trough sales force distribution. Develop more product variants of Fudia Cake & Bakery based on the local source. Strengthen brand equity and develop a remarkable brand image program. Design and setting promotions systematic & massively is a priority.